2021
DOI: 10.1109/ojits.2021.3118972
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Attacks and Defense in Deep Reinforcement Learning (DRL)-Based Traffic Signal Controllers

Abstract: Security attacks on intelligent transportation systems (ITS) may result in life-threatening situations. Combining deep neural networks with reinforcement learning (RL) models called DRL shows promising results when applied to urban Traffic Signal Control (TSC) for adaptive adjustment of traffic light schedules. In this paper, first, we explore the security vulnerabilities of DRL-based TSCs in the presence of adversarial attacks. We investigate the impact of the two distinct threat models with two state-of-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Algorithm 1 summarizes the detailed algorithm steps of DLA. Input x n * to the classifier, calculate the feature loss L f according to (17), and determine the direction of the feature level perturbation according to (18); 4:…”
Section: Double Level Adversarial Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithm 1 summarizes the detailed algorithm steps of DLA. Input x n * to the classifier, calculate the feature loss L f according to (17), and determine the direction of the feature level perturbation according to (18); 4:…”
Section: Double Level Adversarial Attackmentioning
confidence: 99%
“…Since adversarial attack and defense are two parts of a game process, many researchers have designed a defense method against the attack after proposing a new attack method to improve the defense ability of the classifier [15]. For example, in the field of intelligent transportation, researchers have studied the adversarial attack and defense methods of the intelligent recognition model of urban road conditions, and improved the robustness of the model in automatic driving in the field of image recognition [16], [17]. Today, compared with the image field, there is little work to apply adversarial examples to wireless communication, which means that the communication jamming recognition model will be easily attacked.…”
mentioning
confidence: 99%
“…They concluded that when training in scenarios with sensor failures, the RL approach can be quite robust to the wide sensor failure and demand surge problems. Haydari et al (2021) investigated security vulnerabilities in Deep Reinforcement Learning (DRL) based Traffic Signal Control (TSC) systems under adversarial attacks. They explored two threat models using white-box and black-box attacks on different DRL-based TSC algorithms in single and multiple intersections.…”
Section: Robustness In Traffic Signal Controlmentioning
confidence: 99%
“…Recently, Haydari et al, [35] used reinforcement learning based to model attacks on traffic control and study their impacts. They used SUMO simulations and observed anomalous behavior to be detected well.…”
Section: Review Of Past Studiesmentioning
confidence: 99%